Simulation environment for polymeric nanoparticle: experiment database - Zamberlan, Alexandre Oliveira; Dalcin, Ana Júlia Figueiró; Kurtz, Guilherme Chagas; Bordini, Rafael Heitor; Raffin, Renata Platcheck; Fagan, Solange Binotto (Disciplinarum Scientia | Naturais e Tecnológicas, 2017)
Simulations in the Nanoscience area are widely used and the validation processes are generally associated with scientific or mathematical models. This paper shows design and implementation of experiments management module, as part of a simulation environment for nanoparticles. The module is part of a larger project named Multiagent System for Polymeric Nanoparticles (MASPN). The simulations, which have run in MASPN, need validation, so the importance of an experiment database for correlation. This database can support evaluation of stable formulations, behaving as a pattern recognition tool. The simulation environment, such as a software tool, was designed and implemented following the software engineering methodology known as Feature-Driven Development (FDD). The results were the assessment of requirements and system input parameters; modelling and diagramming of MASPN features; system graphical interfaces; particle distribution display (size and position); and normal distribution charts display. Moreover, it is emphasized the possibility of correlation between experimental results and theoretical simulations.